2020
DOI: 10.1002/jcla.23229
|View full text |Cite
|
Sign up to set email alerts
|

The fat mass, estimated glomerular filtration rate, and chronic inflammation in type 2 diabetic patients

Abstract: Type 2 diabetes mellitus (T2DM) is associated with compromised health-related quality of life 1 and premature death from vascular disease and several types of cancers. 2 Insulin resistance is the earliest feature in the development of T2DM. Insulin resistance is induced by obesity, inflammation, 3 and low physical activity. 4 Conversely, physical activity accompanied by weight loss leads to improvement in insulin sensitivity. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A cross‐sectional study in South Africa also showed a positive association between C‐index and insulin resistance 34 . Our findings are consistent with recent studies that indicate women have a higher RFM than men 35 . Differences in physiological structure, metabolism, exercise, and other factors may contribute to the variations in body fat ratio between men and women 36–38 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A cross‐sectional study in South Africa also showed a positive association between C‐index and insulin resistance 34 . Our findings are consistent with recent studies that indicate women have a higher RFM than men 35 . Differences in physiological structure, metabolism, exercise, and other factors may contribute to the variations in body fat ratio between men and women 36–38 .…”
Section: Discussionsupporting
confidence: 90%
“…34 Our findings are consistent with recent studies that indicate women have a higher RFM than men. 35 Differences in physiological structure, metabolism, exercise, and other factors may contribute to the variations in body fat ratio between men and women. [36][37][38] Therefore, the percentage of body fat used to define obesity is higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…A different study by Šálek et al performed on 565 diabetic patients that also used standardized creatinine and cystatin C assays and estimated GFR according to CKD‐EPI equations reported similar results: eGFRcrea results were higher than eGFRcys in the GFR range below 60 mL/min/1.73 m 2 Jabor et al extended the study to 1515 diabetic patients. The study extension confirmed higher eGFRcrea in the GFR range below 60 mL/min/1.73 m 2…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that inflammation induces the progression of NAFLD and increases serum ALT levels 22 . Moreover, body fat mass is positively related to high‐sensitive C‐reactive protein, a general indicator of inflammation 23 …”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, body fat mass is positively related to highsensitive C-reactive protein, a general indicator of inflammation. 23 Currently, serum ALT is widely used not only to assess the development and prognosis of liver disease, but also as a reference with screening overall health status during health check-ups. 24 Hernaez et al 25 reported that individuals with elevated ALT had an increased risk for all-cause and cardiovascular mortality.…”
Section: Ta B L E 1 Characteristics Of the Study Participantsmentioning
confidence: 99%